2015
DOI: 10.1097/mpa.0000000000000344
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lornoxicam on TLR2 and TLR4 Messenger RNA Expression and Tumor Necrosis Factor-α, Interleukin-6, and Interleukin-8 Secretion in Patients With Systemic Complications of Acute Pancreatitis

Abstract: The use of lornoxicam at the onset of acute pancreatitis decreased TLR2 and TLR4 expression and the production of proinflammatory cytokines, thereby reducing the risk of systemic complications and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Despite the lack of conclusive evidence, proton pump inhibitors (PPIs) have been empirically used as the standard therapeutic method for AP in many countries worldwide, including Japan, Korea, China, Italy, and those in Eastern Europe ( Pezzilli et al, 2007 ; Hajjar et al, 2012 ; Xia et al, 2012 ; Yoo et al, 2012 ; Gorsky et al, 2015 ; Murata et al, 2015 ). PPIs act by effectively reducing the quantity of intraluminal acid in the stomach and duodenum, mechanistically by blocking the common terminal pathway for acid secretion, which lies at the H + -K + -adenosine triphosphatase (ATPase) ( Robinson, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the lack of conclusive evidence, proton pump inhibitors (PPIs) have been empirically used as the standard therapeutic method for AP in many countries worldwide, including Japan, Korea, China, Italy, and those in Eastern Europe ( Pezzilli et al, 2007 ; Hajjar et al, 2012 ; Xia et al, 2012 ; Yoo et al, 2012 ; Gorsky et al, 2015 ; Murata et al, 2015 ). PPIs act by effectively reducing the quantity of intraluminal acid in the stomach and duodenum, mechanistically by blocking the common terminal pathway for acid secretion, which lies at the H + -K + -adenosine triphosphatase (ATPase) ( Robinson, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…There were no differences in TLR4 expression between MAP and SAP, however these findings may have been confounded by the use of empiric glucocorticoids in the SAP cohort. These findings are supported by studies of mRNA derived from PBMCs that found high levels of TLR4 and TLR2 transcripts in AP as compared to healthy controls ( 49 , 181 ). In summary, all three studies suggest higher TLR4 activity in AP compared to controls, however they do not determine whether TLR4 expression differs between mild and severe disease.…”
Section: Innate Immune and Inflammatory Responses In Apmentioning
confidence: 53%
“…Knockdown of MYD88 attenuates LPS-induced inflammatory responses in pancreatic ductal cells (24). Meanwhile, acute pancreatitis patients have high level of TLR4 and decreasing the expression of TLR4 reduces the risk of systemic complications and mortality (25). NF-κB and p38MAPK are the two main signaling pathways activated by TLR4-mediated signaling, and both play an important role in the regulation of several inflammatory cytokines and mediators.…”
Section: Discussionmentioning
confidence: 99%